2019
DOI: 10.12659/msm.913826
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Surgery-Based Multidisciplinary Clinical Management of Reninoma: A Single-Center Study

Abstract: Background This article presents our experience in managing a rare kidney tumor – reninoma – by analyzing a relatively large series of cases from a single center. Material/Methods Nine cases of reninoma were reviewed. Clinical manifestations, imaging examinations, laboratory examinations, perioperative data, and pathological findings were summarized. A 58.8-month follow-up was performed to evaluate patient survival and recrudescence. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“… 1 Renal vein sampling (RVS) and renal biopsy (RB) are useful diagnostic investigations. 2 Surgical resection is an effective cure for reninoma and accompanying consequences of renin hypersecretion. 2 , 3 Laparoscopic, nephron sparing surgery yields favourable outcomes for these young patients.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Renal vein sampling (RVS) and renal biopsy (RB) are useful diagnostic investigations. 2 Surgical resection is an effective cure for reninoma and accompanying consequences of renin hypersecretion. 2 , 3 Laparoscopic, nephron sparing surgery yields favourable outcomes for these young patients.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of renin activity in bilateral renal venous blood by selective or segmental renal venous blood sampling may be helpful in diagnosing JGCT; however, it is not recommended clinically due to its high false-negative rate. Previous studies have shown that the positive rate of this test was about 62.5%; meanwhile, in a study of 14 cases of JGCTs in China, it was only 21.4%[ 14 ]. Our case did not use RAAS inhibitors before the test, and blood test showed hypokalemia, hyperreninemia, and elevated aldosterone; ARR was normal, which was consistent with literature reports.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery procedures, including nephron sparing partial nephrectomy for superficial or small lesions and radical nephrectomy for deep or large lesions, are the mainstream treatment options. The safety and long-term efficacy have been proved with numerous evidences ( 2 , 7 , 8 ). However, when it comes to small nodules with difficulty in intraoperative locating, surgery may lead to prolonged warm ischemic time as well as operation time, and renal dysfunction consequently.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment modalities include surgery, ablation, and medical therapy. Surgery is the main option, while the effect of medical therapy is very uncertain, and ablation is not widely used but considered a potential alternative ( 2 , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%